2009
DOI: 10.1111/j.1601-183x.2008.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype differences in cognitive functioning in Noonan syndrome

Abstract: Noonan syndrome (NS) is an autosomal-dominant genetic disorder associated with highly variable features, including heart disease, short stature, minor facial anomalies and learning disabilities. Recent gene discoveries have laid the groundwork for exploring whether variability in the NS phenotype is related to differences at the genetic level. In this study, we examine the influence of both genotype and nongenotypic factors on cognitive functioning. Data are presented from 65 individuals with NS (ages 4-18) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
117
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 28 publications
11
117
1
3
Order By: Relevance
“…Some studies have reported that children with NS have stronger verbal reasoning abilities relative to nonverbal reasoning abilities (Pierpont et al 2009;van der Burgt et al 1999), whereas other studies have found the opposite pattern (D. A. Lee et al 2005) or no significant difference between these domains (Pierpont et al 2015).…”
Section: Intellectual Functioningmentioning
confidence: 79%
See 4 more Smart Citations
“…Some studies have reported that children with NS have stronger verbal reasoning abilities relative to nonverbal reasoning abilities (Pierpont et al 2009;van der Burgt et al 1999), whereas other studies have found the opposite pattern (D. A. Lee et al 2005) or no significant difference between these domains (Pierpont et al 2015).…”
Section: Intellectual Functioningmentioning
confidence: 79%
“…The percentage of individuals with NS scoring in the IQ range associated with intellectual disability (IQ<70) varies from 6 to 23 % across studies (van der Burgt et al 1999;Pierpont et al 2015), representing an increased risk relative to the general population. Despite this increased risk, the majority of people with NS have intellectual functioning within the average range (Pierpont et al 2009;WingbermĂĽhle et al 2012b). It is notable that more recent studies report somewhat higher IQ estimates (Table 3).…”
Section: Intellectual Functioningmentioning
confidence: 90%
See 3 more Smart Citations